Dynamics of Special Needs Assistants’ Roles in the Implementation of Inclusive Education in Elementary Schools - Suci Fitriyani; Ichsan Fauzi Rachman (CV. Yazri Aksara Nusantara, 2025)
Inclusive education in elementary schools requires educators, including Special Needs Assistants (SNAs), to adapt their roles so that students with diverse learning needs receive equitable support. Yet, the expansion of SNA responsibilities often lacks clear professional definitions and institutional reinforcement. This study examines the evolving role of SNAs through a qualitative literature review design. Data were gathered through a systematic search across multiple academic databases using relevant keywords. Identified studies were screened through title and abstract reviews, followed by full-text evaluation to ensure alignment with the research focus. Data were analyzed using thematic analysis to identify patterns in role development and constant comparison to ensure coherence across studies. The findings show that SNA responsibilities have expanded from technical assistance to more complex pedagogical, collaborative, and coordinative functions. However, this evolution remains constrained by limited continuous training, imbalanced student–assistant ratios, restricted resources, and the absence of institutionalized collaboration mechanisms. The study concludes that strengthening professional capacity, enhancing institutional support, and clarifying role expectations are essential to ensure the sustainability and effectiveness of inclusive education in elementary schools.